Master track of POLARSTERN cruise PS149 in 1 sec resolution (zipped, 221 MB) - Marcel Nicolaus (PANGAEA, 2025)
Raw data acquired by position sensors on board RV Polarstern during expedition PS149 was processed to receive a validated master track which can be used as reference of further expedition data. During PS149 two Trimble Marine R750 GPS receivers and the iXBlue HYDRINS hydrographic survey inertial navigation system were used as navigation sensors. Data were downloaded from DAVIS SHIP data base (https://dship.awi.de) with a resolution of 1 sec. Processed data are provided as a master track with 1 sec resolution derived from the position sensors extquotesingle data selected by priority and a generalized track with a reduced set of the most significant positions of the master track.